Pengembangan Bahan Ajar Flipbook Berbasis PJBL Pada Topik Keberagaman Budaya Bangsaku Untuk Meningkatkan Hasil Belajar Siswa Kelas IV SD - Sari, Intan Permata; Novita, Rita; Rahmattullah, Rahmattullah (Jurnal Ragam Pengabdian, 2026)
This study aims to develop flipbook teaching materials based on Project Based Learning (PJBL) on the topic of Cultural Diversity of My Nation to improve the learning outcomes of fourth grade elementary school students. This study uses the Research and Development (R&D) method with the ADDIE model consisting of the stages of Analysis, Design, Development, Implementation, and Evaluation. The subjects of the study were 30 fourth grade students of SDN 31 Banda Aceh. Data collection techniques included validation sheets from material experts, media experts, and language experts, student response questionnaires, and learning outcome tests in the form of pre-tests and post-tests. The results showed that the developed PJBL-based flipbook teaching materials obtained a very good level of feasibility based on validation from material experts of (95) %, media experts of (93) %, and language experts of (93) %, so it was declared very suitable for use in learning. Student responses to the use of flipbooks obtained a percentage of 90% with a very good category. Student learning outcomes increased with an average pre-test score of 64 and a post-test score of 89.3. The N-Gain analysis showed an average value of 73.6%, which is categorized as quite effective. The results of the normality test showed that the data were not normally distributed (p < 0.05), so the analysis was continued using the Wilcoxon Signed Rank Test. The results of the Wilcoxon test showed an Asymp. value of 0.001 (< 0.05), which indicates a significant difference between the pre-test and post-test scores. Thus, the PJBL-based flipbook teaching material was declared feasible and effective in improving student learning outcomes on the topic of Cultural Diversity of My Nation.